Patient-Derived Orthotopic Xenograft Models of Pediatric Brain Tumors: In a Mature Phase or Still in Its Infancy? - Hermans, Eva; Hulleman, Esther (Frontiers in Oncology, 2020)
In recent years, molecular profiling has led to the discovery of an increasing number of brain tumor subtypes, and associated therapeutic targets. These molecular features have been incorporated in the 2016 new World Health Organization (WHO) Classification of Tumors of the Central Nervous System (CNS), which now distinguishes tumor subgroups not only histologically, but also based on molecular characteristics. However, despite the improved diagnosis of (pediatric) tumors in the CNS, the survival of children with a malignant brain tumor still is far worse than for those suffering from other types of malignancies, and new subgroup-specific treatments need to be developed. Here, we give an overview of the currently available orthotopic xenograft models for pediatric brain tumor subtypes as defined by the 2016 WHO classification, to facilitate the choice of appropriate animal models for the preclinical testing of novel treatment strategies, and to provide insight into the current gaps and challenges.